Provision of Family Maintenance From The Income of Fighting Cocks: The Perspective of Saddu Az-Zari'ah - Siregar, Linda Sari Bulan; Taufan, Taufan; Sulastri, Widia; Khairi, Muhammad; Samsurizal, Samsurizal; Hertasmaldi, Hertasmaldi (Samara: Journal of Islamic Law and Family Studies, 2024)
This research aims to analyze the law of providing family support from income from raising fighting cocks from Saddu Az-Zari'ah's perspective. This research uses a qualitative method with a descriptive approach and an empirical juridical legal approach. Data collection techniques include observation, interviews, and documentation. The results of the research can be concluded that the law regarding family support from income from raising fighting cocks in Saddu Az-Zari'ah's view is considered haram. Because, includes bad actions that lead people to immoral acts, as stated in the provisions of Saddu Az-Zari'ah to determine the legal means (means) that prohibit it. If the result of an action brings benefit as taught by the Shari'a, then this method is permissible, and conversely, if the result of an action is detrimental, even though the aim is for good (supporting the family) then it is considered haram.